Pre-trial detention of children : An analysis of Malaysian Law with reference to the international standards - Aminuddin, Mustaffa; Nazli Ismail, Nawang (2016)
Pre-trial detention of any individual charged with crime is consistently viewed by many legal scholars as a controversial issue.This practice has been heavily criticized as it imposes legal punishment of a person not yet convicted of a crime . It deliberately amount to violation of a cardinalprinciple of criminal justice which maintain that a person in presumed innocent until proven guilty. In Malaysia, a growth in population of children detained at the pre-trial stage of criminal process hasbecome a matter of great concern. This article will comparativelyanalyse Malaysian current law and practice on this particular area with reference to the international standards. In addition, this paper also will attempt to highlight any imprecision or shortcoming of the current Malaysian legal framework and propose possible suggestions for its improvement.